Rural development - Pain, Adam; Hansen, Kjell (Abingdon, Oxon Routledge, 2019)
Rural Development is a textbook that critically examines economic, social and cultural aspects of rural development efforts both in the global north and in the global south. By consistently using examples from the north and the south the book highlights similarities of processes as well as differences in contexts.

The authors’ knowledge of Afghanistan and Sweden respectively creates a core for the discussions which are complemented with a wide range of other empirical examples. Rural Development is divided into nine chapters, each with a thematic focus, ranging from concepts and theories through rural livelihoods and natural resources to discussions on policy and processes of change. The book sees rural development as a multi-level, multi-actor and multi-faceted subject area that needs multidisciplinary perspectives both to support it and to analyse it. Throughout the book examples of rural development interventions are discussed using analytical concepts such as power, discourse, consequences and context to grasp rural development as practices that are more than what is presented in policy documents.

The book is written in a way that makes it accessible for undergraduates while at the same time caters for the kind of deeper reading used by master students and Ph.D.’s. Every chapter is linked to discussion questions as well as suggested further readings and useful websites.-- Back cover.
Includes bibliographical references (pages 293-308) and index.
Keywords: Regional planning; Rural development